Analisis Sastra Siber Pada Puisi “Asmaraloka di Sepotong Senja” Karya Ibnu Fatih Dengan Pendekatan Semiotika - Siti Astri Karism; Windi Anggiani (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This study discusses the analysis of cyber literature in the poem "Asmaraloka di Sepotong Senja" by Ibnu Fatih through a semiotic approach. This study aims to reveal the meaning contained in the poem using Roland Barthes' semiotic approach, such as denotative, connotative, and mythical meanings, while analyzing how digital elements such as hypertext and hyperlinks. The method used is qualitative descriptive with semiotic theory as the basis for analysis. Data were obtained from words in the poem that were analyzed in depth. The results of the study show that this poem contains longing in the twilight atmosphere with poetic emotional nuances. Denotatively, the poem describes hope and separation, connotatively there is a deep meaning about the steadfastness of love. Meanwhile, the myth implied in the poem is related to spiritual values in meetings and separations. This study confirms that cyber literature is able to expand the meaning of poetry and the semiotic approach is an effective tool in describing the meaning.